Análisis no paramétrico de rankings de tolerancia en comportamientos moralmente cuestionables - Merino Soto, César (2015)
The aim of this study is to explore, through rankings, tolerance towards morally debatable situations. The sample comprised 254 psychology college students (male and female) in Lima, 21-year old on average. The instrument used was the Morally Debatable Behaviors Scale. It is concluded that there is a similarity in the rankings by gender and age. In terms of religion, there are differences with the group of Evangelists, who are less tolerant than Catholics regarding pre-marital sexual relations. The impact of these results in understanding the tendency to action in terms of morality is discussed.